An E1‐Catalyzed Chemoenzymatic Strategy to Isopeptide‐N‐Ethylated Deubiquitylase‐Resistant Ubiquitin Probes. (27th May 2020) - Zheng, Qingyun; Wang, Tian; Chu, Guo‐Chao; Zuo, Chong; Zhao, Rui; Sui, Xin; Ye, Linzhi; Yu, Yuanyuan; Chen, Jingnan; Wu, Xiangwei; Zhang, Wenhao; Deng, Haiteng; et al.
Abstract: Triazole‐based deubiquitylase (DUB)‐resistant ubiquitin (Ub) probes have recently emerged as effective tools for the discovery of Ub chain‐specific interactors in proteomic studies, but their structural diversity is limited. A new family of DUB‐resistant Ub probes is reported based on isopeptide‐ N ‐ethylated dimeric or polymeric Ub chains, which can be efficiently prepared by a one‐pot, ubiquitin‐activating enzyme (E1)‐catalyzed condensation reaction of recombinant Ub precursors to give various homotypic and even branched Ub probes at multi‐milligram scale. Proteomic studies using label‐free quantitative (LFQ) MS indicated that the isopeptide‐ N ‐ethylated Ub probes may complement the triazole‐based probes in the study of Ub interactome. Our study highlights the utility of modern protein synthetic chemistry to develop structurally and new families of tool molecules needed for proteomic studies. Abstract : DUBstep : A new class of deubiquitylase (DUB)‐resistant ubiquitin (Ub) probes, wherein an N ‐ethyl group is present at the isopeptide bonds, has been developed and used to study the Ub‐interacting (Ubi) proteome. This family of Ub probes can be efficiently prepared by an enzyme‐catalyzed chemoenzymatic strategy using readily available recombinant materials.